Itinéraires d'hommes, trajectoires d'objets Mélanges offerts à Daniele Vitali - Esposito, Arianna; Delferrière, Nicolas; Fochesato, Andrea (Histoires, 2021)
This work brings together twenty-two unpublished contributions written by French and foreign friends and colleagues, as well as former students, to pay homage to Daniele Vitali when he retired. Their thematic diversity reflects the wide spectrum of the research he undertook and shared during a prolific career. They present his legacy all while defining new perspectives. Vitali left his mark on European Celtic archaeology as an associate professor of pre-protohistory and holder of the Celtic archaeology and antiquities chair at the University of Bologne (1998-2009), as a member of the international chair at the Collège de France (2006-2007), then as a professor of classical archaeology at the University of Bourgogne (2010-2018).